Expression of secreted protein acidic and rich in cysteine is an independent prognostic indicator of a poor clinical outcome in oropharyngeal carcinoma patients. (1st February 2016) - Yoshida, Shinya; Wakisaka, Naohiro; Kondo, Satoru; Moriyama-Kita, Makiko; Hirai, Nobuyuki; Endo, Kazuhira; Tsuji, Akira; Nakanishi, Yosuke; Murono, Shigeyuki; Yoshizaki, Tomokazu
Abstract: Conclusion : SPARC-expression is an indicator of the prognosis in terms of OS, independent of HPV-infection. HPV-negative patients with SPARC-Low show survival as favorable as HPV-positive patients, probably because of their higher salvage rate after relapse than SPARC-High patients. Objective : The objectives of the study were to clarify the correlation between the expression of secreted protein acidic and rich in cysteine (SPARC) and HPV-status, and to determine the prognostic value of SPARC-expression in oropharyngeal squamous cell carcinoma (OPSCC) patients. Methods : Fifty-three formalin-fixed and paraffin-embedded tissues were obtained from patients with OPSCC who underwent curative treatment. The SPARC protein was detected by immunohistochemistry. SPARC-expression level was divided into two categories, SPARC-High and SPARC-Low, according to the staining index. Results : Twenty-two out of the 53 OPSCC patients were HPV-positive. There was no significant correlation between the HPV-status and SPARC-expression level. Multivariate Cox proportional hazards regression analysis revealed that the HPV-status and SPARC-expression are independent prognostic indicators of favorable and unfavorable overall survival (OS) ( p  = 0.021 and p  = 0.012), respectively. For disease-free survival, the HPV-status was the only predictive factor ( p  = 0.022). After stratification by the HPV-status, high SPARC-expression was a significant predictor of poor OS in HPV-negative OPSCC patients using Kaplan–Meier analysis and the log-rank test ( p  = 0.014). Ten out of 28 SPARC-Low patients relapsed, among which six patients (60%) were salvaged. However, 14 out of 25 SPARC-High patients relapsed, and only three patients (21.4%) were salvaged.